The time-place maze: A novel behavioral apparatus for assessing integrated spatial-temporal processing in rats - Fazel Isapanah Amlashi; Ali Ashkbari; Mehrdad Jahanshahi; Ahmad Sohrabi; Siavash Ahmadi-Noorbakhsh (PLoS ONE, 2026)
Behavioral paradigms used to study hippocampal place and time cells typically focus on the perception of either space or time in isolation, rather than the interaction between these two dimensions. To address this gap, we developed the Time-Place Maze (TPM)s, a novel behavioral apparatus designed to require rats to integrate their perception of both spatial and temporal cues to obtain a reward. The maze consists of a start box (it consist Time-door), a reward box, and two connecting bridges of differing lengths. At the beginning of the task, the time-door opens with one of two possible delays: either 0 seconds or 3 seconds. In The short delay (0s) the short path is open to reward, and in the longer delay (3s) the long path is open. The TPM protocol includes three sequential phases: training, screening, and the main experimental phase. During the training phase, rats underwent four daily sessions. In the final phase, each rat completed 100 randomized tests designed to assess integration of time and place information in decision-making. Six adults male Wistar rats (weighing 230 ± 20 g) were included in the training phase; four met the screening criteria and progressed to the main phase. On average, rats required 16.25 corrective interventions during training. In the main phase, success rates across 100 trials ranged from 73% to 82%. Importantly, the total number of corrections in the main phase was significantly associated with overall task success (p = 0.019). These findings support the feasibility and utility of the TPM in animal models. The task provides unique opportunities in behavioral neuroscience research.